Role Analysis of Distributed Generation Towards Transmission Expansion Planning Using MILP - Gessa Firman Febrian; Sasongko Pramono Hadi; Sarjiya Sarjiya (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
Electricity demand increase as function of population and economic activity growth. To meet the demand growth, one kind of approaches to expand electrical system is to calculate the need of generating unit and the result will be used to determine the needs of transmission line. In this research, a model was developed with focused on transmission line expansion based on Mix Integer Linear Programming method. The objective function was to minimize overall investment cost for transmission and operating cost of all generating units. The developed model was implemented in 6-bus Garver’s test system. Distributed generation implementation impact is also studied in this study in term of network configuration and overall expansion cost. The results show that distributed generation implementation will differ the network configuration and reduce the overall system cost, with overall system cost with and without distributed generation implementation was 106.4 million and 103.18 million respectively.